Pursuing justice against the abuse of power by the rich through social media: A case study. Issue 1 (2nd January 2016) - Kim, Dongho; Youn, Myoung-Kil
ABSTRACT: The purpose of this case study is to compare and contrast two recent legal cases and to derive practical implications to promote social justice in terms of income inequality. This study focuses on exploring and analyzing two of the most recent legal cases of the abuse of power by the rich in order to identify the effects of social media on these types of cases. Despite the availability of many studies and findings about the tolerance level to income inequality, the following logic is more appropriate in applying and analyzing the two cases: If people don't know, see, or experience the abuse of the rich or income inequality, they are more tolerant of the abuse and income inequality. Based on the analysis of the two cases, the article concludes that these two cases are not the usual air rage cases; they are more about the abuse of the rich and the punishment decided by the use of technology.